UMPSA Advanced and Jakarta Business School strengthen strategic partnership - Mohammad Syafiq Syahmi, Suhaimi (UMPSA, 2025)
JAKARTA, 31 January 2025 – UMPSA Advanced and Jakarta Business School (JBS) have strengthened their strategic partnership with the inaugural courtesy visit by the Board of Directors of UMPSA Advanced to JBS as part of efforts to reinforce academic and strategic collaboration between both institutions of higher learning.